Environmentally committed short-term planning of electrical distribution systems considering renewable based DG siting and sizing - Dominguez, Ozy D. Melgar [UNESP]; Pourakbari-Kasmaei, Mahdi [UNESP]; Mantovani, Jose Roberto Sanches [UNESP]; Lavorato, Marina (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper proposes an environmentally committed mixed-integer linear programming (MILP) model to find the best plan for the electrical distribution systems (EDSs) in a short-term planning horizon. In this regard, the energy delivered by the substation and the total investment cost are minimized while the stochasticity related with the demand and photovoltaic (PV) generation is modeled via external uncertainty indexes. Considering PV generation, switchable and fixed capacitor banks (CBs), voltage regulators (VRs), conductor replacement, as well as operating costs results in a mixed-integer nonlinear programming (MINLP) model. However, to obtain the globally optimal solution, this highly nonlinear model, using appropriate linearization techniques, is recast to an MILP model. In order to validate and show the effectiveness of the proposed model, a 42-node system is considered in detail.
Keywords: Environmentally committed plan; External uncertainty indexes; Mixed-integer linear programming; Short-term planning